Experimental Investigation On The Effect Of Epoxy On The Encapsulation Process In Light Emitting Diode Manufacturing - Muniary, Kaalidass (Universiti Sains Malaysia, 2021)
The electronic sector is developing novel products that are smaller and faster, with better performance, a lighter container, and are more cost effective. An integrated circuit can be used to link several LEDs with different functions to electronic devices packaged. The area between the cover lens and the LED chip is filled with a non-conductive polymeric substance, which is commonly epoxy or transparent silicone encapsulant. The purpose of encapsulation is to shield the device from mechanical effects that could weaken the connection between the chip and the substrate. The research is focussing on experimental investigation on the effect of epoxy on the encapsulation process in LED. The different parameters that effect the encapsulation process, such as needle size, type of epoxy resin and method of curing have been studied. The contact angle, contact surface area and hardness of each type of epoxy were measured after the curing process. The three types of epoxy resin with the hardener are injected onto the wafer substrate manually with a syringe and five types of needle size. The contact angle and surface area of contact measurement were done by the ImageJ software and hardness test in the nanoindentation lab. The experimental results showed the 1:1 self-curing epoxy resin is the most efficient type of epoxy resin as it has the relevant values for contact angles and surface area of contact. The 21G needle size was chosen as the suitable size for the encapsulation process. The selection of the right epoxy is determined by the contact angle and surface area of contact measurements for this project. The hardness test was conducted for the oven curing epoxy resin.